Re-Visiting the Embryogenesis of the Human Lower Lip: An Overlooked Paradigm - Vastardis, Heleni; Spyropoulos, Meropi N. (Frontiers in Physiology, 2012)
The rare opportunity to study a human fetus showing bilateral clefting of the lower lip along with other associated anomalies resembling those of the equally rare Pena-Shokeir phenotype prompts this report. The scarcity of reports on bilateral clefts of the lower lip has strengthened the conventional understanding or, perhaps even dogma that the lower lip and jaw develop from the progressive midline merging of just two mandibular prominences in the embryo. On the basis of observations stemming from this case report, it is proposed that yet another developmental event or process (in addition to the midline merging of the mandibular prominences) may be operable in the normal morphogenesis of the lower lip and anterior mandibular region. The bilateral paramedian clefting observed provides evidence that another distinct developmental region, a small medial process complements mandibular morphogenesis.